Anti-crack plant fiber concrete and preparation method thereof

By chemically treating coconut fibers and introducing fly ash, a crack-resistant plant fiber concrete was prepared, which solved the problems of high brittleness and environmental impact of traditional concrete, and achieved efficient resource utilization and low-carbon and environmental protection.

CN119822722APending Publication Date: 2025-04-15CHINA CONSTR 4TH ENG BUREAU 6TH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411949446.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional concrete has high brittleness, low tensile and flexural properties, which are prone to cracks, affecting the safety and service life of the structure. At the same time, the production process of steel fibers and synthetic fibers consumes a lot of environmental and resources, and is costly.

Method used

By chemically treating coconut fibers, it enhances its tensile properties and interface bonding with cement matrix, and introduces industrial solid waste such as fly ash to prepare a crack-resistant plant fiber concrete. The method includes multi-step chemical modification treatment to improve the performance of coconut fibers and reduce cement usage through fly ash and reduce carbon emissions.

Benefits of technology

Improves the crack resistance and durability of concrete, extends the service life of buildings, reduces resource consumption and carbon emissions required for maintenance and reconstruction, and reduces carbon dioxide emissions during building materials production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to anti-crack plant fiber concrete and a preparation method thereof, and belongs to the technical field of building materials. The anti-crack plant fiber concrete is prepared from cement, fine aggregate, coarse aggregate, modified coconut fiber, mineral powder, fly ash, a water reducing agent, an air entraining agent, an expanding agent and water as raw materials. The preparation method comprises the following steps: adding insoluble dry materials into a forced mixer, carrying out dry mixing to obtain a mixture, dissolving the water-soluble admixture with deionized water, carrying out uniform stirring, adding the obtained mixture into the mixture, and carrying out wet mixing to obtain a concrete mixture. According to the preparation method disclosed by the invention, the anti-crack concrete is prepared from the renewable coconut fibers, so that the dependence on synthetic fibers and steel is reduced, the carbon emission is reduced, and the preparation method is low-carbon and environment-friendly; the prepared concrete material is not easy to crack, and has good impact resistance and shear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a crack-resistant plant fiber concrete and a preparation method thereof. Background Art

[0002] As a major material widely used in civil engineering and construction, concrete has good compressive resistance and durability. However, traditional concrete has the defects of high brittleness, low tensile and flexural properties, and is prone to cracks under load, temperature changes, and shrinkage, which affects the safety and service life of the structure. Therefore, improving the crack resistance of concrete has become a focus of attention in the engineering community.

[0003] Fiber reinforced concrete (FRC) is a new type of material that improves the mechanical properties of concrete by adding fibers. Commonly used fibers include steel fibers, glass fibers, and synthetic fibers. Although these fibers improve the crack resistance and toughness of concrete to a certain extent, there are also some problems: High cost: The production cost of steel fiber and synthetic fiber is high, which limits their application in large-scale projects.

[0004] Environmental impact: The production and use of steel fibers consume high energy and are prone to corrosion, which increases maintenance costs; synthetic fibers are mostly petrochemical products, and the production process will produce a large amount of greenhouse gases, which has an adverse impact on the environment.

[0005] High carbon emissions: The manufacturing process of steel fiber and synthetic fiber emits a large amount of carbon dioxide.

[0006] Researchers have turned their attention to natural plant fibers. Plant fibers have the advantages of wide sources, renewable, low cost, light weight and environmental protection. Among them, coconut fiber, as a high-quality natural fiber, has good tensile strength and toughness, corrosion resistance and wear resistance. In addition, coconut fiber is biodegradable and can reduce pollution to the environment. Its application is in line with the concept of green and low-carbon development.

[0007] However, applying coconut fiber directly to concrete also has its challenges: Insufficient interfacial bonding: The surface of coconut fiber is smooth and highly hydrophilic, but the bonding strength between it and the cement matrix is ​​weak, which affects the reinforcement effect.

[0008] Durability issues: Untreated coconut fiber tends to degrade in alkaline environments, affecting the long-term performance of concrete.

[0009] On the other hand, with the development of industry, a large amount of industrial solid waste (such as fly ash) is generated. If it is not effectively utilized, it will not only cause a waste of resources, but also cause environmental pollution. Fly ash has a certain volcanic ash activity. Reasonable use of fly ash to replace part of cement can not only improve the performance of concrete, but also reduce the amount of cement used and reduce the emission of carbon dioxide in the cement production process.

[0010] Cement production is an industry with high energy consumption and high emissions. Reducing cement consumption is of great significance to reducing the carbon footprint of the construction industry. Therefore, how to achieve resource recycling and carbon emission reduction while improving the performance of concrete has become a technical problem that needs to be solved urgently.

[0011] Based on this, the present invention aims to prepare a fiber-reinforced concrete with excellent performance, economy and environmental protection by effectively chemically treating coconut fiber to enhance its tensile properties and interface bonding with cement matrix, and introducing industrial solid waste such as fly ash. This concrete material can not only improve the crack resistance and durability of the structure, extend the service life of the building, reduce the resource consumption and carbon emissions required for maintenance and reconstruction, but also directly reduce the carbon dioxide emissions in the production process of building materials by reducing the amount of cement and utilizing waste, which has significant environmental benefits and social value. Summary of the invention

[0012] The object of the present invention is to provide a crack-resistant plant fiber concrete and a preparation method thereof, so as to solve the problems mentioned in the above background technology.

[0013] The purpose of the present invention can be achieved through the following technical solutions: A crack-resistant plant fiber concrete comprises the following raw materials in parts by weight: 230 parts of cement, 826 parts of fine aggregate, 985 parts of coarse aggregate, 23.2 parts of modified coconut fiber, 72 parts of mineral powder, 55 parts of fly ash, 7.5 parts of water reducer, 0.9 parts of air entraining agent, 23 parts of expansion agent, and 121 parts of water; A method for preparing crack-resistant plant fiber concrete comprises the following steps: The first step is to weigh the raw materials according to the mass proportions: 230 parts of cement, 826 parts of fine aggregate, 985 parts of coarse aggregate, 23.2 parts of modified coconut fiber, 72 parts of mineral powder, 55 parts of fly ash, 7.5 parts of water reducer, 0.9 parts of air entraining agent, 23 parts of expansion agent, and 121 parts of water; Step 2: Add cement, mineral powder, fly ash, fine aggregate and coarse aggregate into a forced mixer, dry mix for 30 seconds, add modified coconut fiber after mixing evenly, and continue dry mixing for 1-2 minutes to obtain a mixture; Step 3: Dissolve the water reducing agent, air entraining agent and expansion agent with deionized water, stir them evenly, then add them into the forced mixer filled with the mixture, and wet mix for 1-2 minutes to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers, and vibrate and compact each layer of concrete mixture after pouring; Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

[0014] Furthermore, the cement is PO 42.5 grade ordinary Portland cement, the fine aggregate is natural sand, the coarse aggregate is 5mm-31.5mm continuously graded crushed stone, the mineral powder is S95 grade slag powder, the fly ash is Class F Class I fly ash, the water reducer is RAWY101 type polycarboxylic acid high performance water reducer, the air entraining agent is FX-9 type air entraining agent, and the expansion agent is UEA expansion agent.

[0015] Furthermore, in the fourth step, the height of each layer of concrete after pouring is half of the test mold height.

[0016] Furthermore, the modified coconut fiber is prepared by the following steps.

[0017] Step 1, 2-chloromethylbenzoic acid and phosphorous acid are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, the system temperature is raised to 80-90° C., concentrated sulfuric acid is added dropwise to the three-necked flask, and after the addition is completed, the reaction is continued at a temperature of 80-90° C. for 30 minutes. After the reaction is completed, the reaction solution is poured into deionized water for cooling and precipitation, and then vacuum filtered, and the obtained solid is recrystallized and dried to obtain a modifier; Step 2, the cut coconut fiber and the sodium hydroxide solution are mixed in a three-necked flask, magnetic stirring is turned on, and the mixture is reacted for 1 hour at room temperature for alkalization treatment, after which the coconut fiber is filtered out, washed with deionized water and dried to obtain alkalized coconut fiber, and the alkalized coconut fiber is added to a three-necked flask filled with a hydrogen peroxide solution, magnetic stirring is turned on, and the mixture is reacted for 2 hours for oxidation treatment under outdoor conditions, after which the coconut fiber is filtered out, washed with deionized water and dried to obtain oxidatively modified coconut fiber; Step 3, the oxidatively modified coconut fiber and the isopropanol solution of the modifier are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the reaction is carried out at a temperature of 50-60° C. for 1.5 hours. After the reaction is completed, the coconut fiber is filtered out, washed with deionized water, then washed with anhydrous ethanol and dried to obtain etherified coconut fiber; Step 4, etherified coconut fiber, acrylic acid, acrylamide, and deionized water are mixed in a three-necked flask, a condenser and a thermometer are installed, and magnetic stirring is turned on. Potassium persulfate and methylene bisacrylamide are then added to the three-necked flask. After the addition, the system temperature is raised to 60-70° C., and the reaction is carried out at a temperature of 60-70° C. for 1-2 hours. After the reaction is completed, the coconut fiber is filtered out, washed with deionized water, and then dried to obtain water-absorbing modified coconut fiber; Step 5, modifying the water-absorbent modified coconut fiber with low-temperature oxygen plasma, adding the modified coconut fiber to a beaker containing an ethanol solution of a silane coupling agent, adjusting the pH to 4-5 with glacial acetic acid, soaking the coconut fiber at room temperature for 1-2 hours, filtering out the coconut fiber, washing the coconut fiber with deionized water, and drying the coconut fiber to obtain a silane coupling agent modified coconut fiber; Step 6: Soak the coconut fiber modified by the silane coupling agent in a beaker containing the nanomaterial dispersion, filter out the coconut fiber after ultrasonic treatment, and dry it to obtain the modified coconut fiber.

[0018] Furthermore, the concentrated sulfuric acid used in step 1 is concentrated sulfuric acid with a mass fraction of 98%, and the amount ratio of 2-chloromethylbenzoic acid, phosphorous acid and concentrated sulfuric acid used is 0.1 mol: 0.01 mol: 11-13 g.

[0019] Furthermore, in step 2, the specification of the coconut fiber after cutting is 20-30 mm, the sodium hydroxide solution used is a sodium hydroxide aqueous solution with a mass fraction of 5%, and the mass ratio of the cut coconut fiber to the sodium hydroxide solution is 1:15; the hydrogen peroxide solution used is a hydrogen peroxide aqueous solution with a mass fraction of 3%, and the mass ratio of the alkalized coconut fiber to the hydrogen peroxide solution is 1:20.

[0020] Furthermore, the mass fraction of the isopropanol solution of the modifier used in step 3 is 20%, and the mass ratio of the oxidatively modified coconut fiber and the isopropanol solution of the modifier used is 7:15.

[0021] Furthermore, the amount ratio of etherified coconut fiber, acrylic acid, acrylamide, deionized water, potassium persulfate and methylene bisacrylamide used in step 4 is 20g:48-52g:6-9.6g:100-120mL:1.28g:0.02g.

[0022] Furthermore, in step 5, the conditions for oxygen plasma modification are a power of 100 W and a modification time of 5-15 min.

[0023] Furthermore, in step 5, the mass fraction of the solute silane coupling agent in the ethanol solution of the silane coupling agent is 1%, the solvent is an ethanol aqueous solution with a volume fraction of 95%, the silane coupling agent used is obtained by mixing KH-550 and a titanate coupling agent NDZ-201 in a mass ratio of 1:1, and the mass ratio of the water-absorbent modified coconut fiber and the silane coupling agent used is 1:6.

[0024] Furthermore, the nanomaterial described in step 6 is one of nano silicon dioxide and nano aluminum oxide, the dispersant used for the nanomaterial dispersion is polyvinyl pyrrolidone, and the solvent is deionized water, wherein the mass fraction of the nanomaterial is 0.5%, the mass fraction of the dispersant is 1-5%, the mass ratio of the silane coupling agent modified coconut fiber to the nanomaterial is 1:4-5, the immersion time is 2h, and the ultrasonic dispersion time is 0.5h.

[0025] Beneficial effects of the present invention: 1) The present invention uses cement, fine aggregate, coarse aggregate, modified coconut fiber, mineral powder, fly ash, water reducer, air entraining agent, expansion agent and water as raw materials to prepare a crack-resistant plant fiber concrete; the preparation method of the present invention comprises the following steps: firstly adding insoluble dry materials into a forced mixer and dry-mixing to obtain a mixture; then dissolving a water-soluble admixture with deionizer, stirring the mixture evenly, and then adding the mixture into the mixture and wet-mixing to obtain a concrete mixture; finally, the concrete mixture is layered poured and vibrated to be compacted, and then placed to be demoulded and cured to obtain a crack-resistant plant fiber concrete; the coconut fibers inside the crack-resistant plant fiber concrete of the present invention form a three-dimensionally distributed network structure, which can hinder the generation and expansion of cracks and improve the crack resistance and impact resistance of the concrete.

[0026] 2) The present invention first uses 2-chloromethylbenzoic acid as a raw material, uses concentrated sulfuric acid as a sulfonating agent, and uses phosphorous acid as a catalyst to prepare a reinforcing agent through a sulfonation reaction, and then treats coconut fiber with alkali, oxidation, and etherification with a modifier, and then uses acrylic acid and acrylamide to perform water absorption modification to obtain a coconut fiber-based super absorbent resin, and then the water-absorbent modified coconut fiber is modified with low-temperature oxygen plasma, treated with a silane coupling agent, and immersed in a nano material dispersion to obtain a modified coconut fiber. The modified coconut fiber of the present invention has good water absorption, can absorb and store a large amount of water, inhibits the shrinkage deformation of concrete, and reduces the possibility of concrete cracking. In addition, the sulfonic acid group on the surface of the coconut fiber after the etherification treatment can also be hydrolyzed to form a charged anchoring group to improve the dispersibility of the coconut fiber, improve the disadvantage that the coconut fiber is easy to agglomerate, and has good bonding ability with the concrete substrate and good strength.

[0027] 3) The preparation method of the present invention utilizes renewable coconut fiber to prepare crack-resistant concrete, which reduces the dependence on synthetic fibers and steel, reduces carbon emissions, and is low-carbon and environmentally friendly. The prepared concrete material is not easy to crack and has good impact resistance and shear resistance. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1 A modified coconut fiber is prepared by the following steps: Step 1, 0.1 mol 2-chloromethylbenzoic acid and 0.01 mol phosphorous acid are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, the system temperature is raised to 80°C, 11 g concentrated sulfuric acid is added dropwise to the three-necked flask, and after the addition is completed, the reaction is continued at a temperature of 80°C for 30 minutes. After the reaction is completed, the reaction solution is poured into deionized water for cooling and precipitation, and then vacuum filtered, and the obtained solid is recrystallized and dried to obtain a modifier; Step 2, the coconut fiber cut into 20mm and the sodium hydroxide solution with a mass fraction of 5% are mixed in a three-necked flask at a mass ratio of 1:15, the magnetic stirring is turned on, and the reaction is carried out at room temperature for 1h for alkalization treatment, and then the coconut fiber is filtered out, washed with deionized water and dried to obtain alkalized coconut fiber, and then the alkalized coconut fiber and the hydrogen peroxide solution with a mass fraction of 3% are mixed in a three-necked flask at a mass ratio of 1:20, the magnetic stirring is turned on, and the reaction is carried out under outdoor conditions for 2h for oxidation treatment, and then the coconut fiber is filtered out, washed with deionized water and dried to obtain oxidatively modified coconut fiber; Step 3, the oxidatively modified coconut fiber and the isopropanol solution of the modifier with a mass fraction of 20% are mixed in a three-necked flask in a mass ratio of 7:15, magnetic stirring is turned on, and the reaction is carried out at a temperature of 50° C. for 1.5 hours. After the reaction is completed, the coconut fiber is filtered out, washed with deionized water, then washed with anhydrous ethanol and dried to obtain etherified coconut fiber; Step 4, 20g etherified coconut fiber, 48g acrylic acid, 6g acrylamide, and 100mL deionized water were mixed in a three-necked flask, a condenser and a thermometer were installed, and magnetic stirring was turned on. Then, 1.28g potassium persulfate and 0.02g methylene bisacrylamide were added to the three-necked flask. After the addition, the system temperature was raised to 60°C, and the reaction was carried out at a temperature of 60°C for 1h. After the reaction was completed, the coconut fiber was filtered out, washed with deionized water, and then dried to obtain water-absorbent modified coconut fiber; Step 5, modifying the water-absorbent modified coconut fiber with low-temperature oxygen plasma, adding it to a beaker containing an ethanol solution of a silane coupling agent, and adjusting the pH to 4 with glacial acetic acid. After soaking for 1 hour at room temperature, filtering out the coconut fiber, washing it with deionized water, and drying it to obtain a silane coupling agent-modified coconut fiber. In this step, the mass fraction of the solute silane coupling agent in the ethanol solution of the silane coupling agent is 1%, and the solvent is an ethanol aqueous solution with a volume fraction of 95%. The silane coupling agent used is obtained by mixing KH-550 and a titanate coupling agent NDZ-201 in a mass fraction ratio of 1:1, and the mass fraction ratio of the water-absorbent modified coconut fiber and the silane coupling agent used is 1:6; Step 6, soaking the coconut fiber modified by the silane coupling agent in a beaker containing a nano-silicon dioxide dispersion for 2 hours, filtering out the coconut fiber after ultrasonic treatment for 0.5 hours and drying to obtain modified coconut fiber, wherein the dispersant used for the nano-silicon dioxide dispersion is polyvinyl pyrrolidone, the solvent is deionized water, wherein the mass fraction of nano-silicon dioxide is 0.5%, the mass fraction of the dispersant is 1%, and the mass ratio of the used silane coupling agent modified coconut fiber to the nano material is 1:4.

[0030] Example 2 A modified coconut fiber is prepared by the following steps: Step 1, 0.1 mol 2-chloromethylbenzoic acid and 0.01 mol phosphorous acid are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, the system temperature is raised to 85°C, 12 g concentrated sulfuric acid is added dropwise to the three-necked flask, and after the addition is completed, the reaction is continued at a temperature of 85°C for 30 minutes. After the reaction is completed, the reaction solution is poured into deionized water to cool and precipitate, and then vacuum filtered, and the obtained solid is recrystallized and dried to obtain a modifier; Step 2, the coconut fiber cut into 25mm and the sodium hydroxide solution with a mass fraction of 5% are mixed in a three-necked flask at a mass ratio of 1:15, the magnetic stirring is turned on, and the reaction is carried out at room temperature for 1h for alkalization treatment, and then the coconut fiber is filtered out, washed with deionized water and dried to obtain alkalized coconut fiber, and then the alkalized coconut fiber and the hydrogen peroxide solution with a mass fraction of 3% are mixed in a three-necked flask at a mass ratio of 1:20, the magnetic stirring is turned on, and the reaction is carried out under outdoor conditions for 2h for oxidation treatment, and then the coconut fiber is filtered out, washed with deionized water and dried to obtain oxidatively modified coconut fiber; Step 3, the oxidatively modified coconut fiber and the isopropanol solution of the modifier with a mass fraction of 20% are mixed in a three-necked flask in a mass ratio of 7:15, magnetic stirring is turned on, and the reaction is carried out at a temperature of 55° C. for 1.5 hours. After the reaction is completed, the coconut fiber is filtered out, washed with deionized water, washed with anhydrous ethanol, and dried to obtain etherified coconut fiber; Step 4, 20g etherified coconut fiber, 50g acrylic acid, 7.8g acrylamide, and 110mL deionized water were mixed in a three-necked flask, a condenser and a thermometer were installed, and magnetic stirring was turned on. Then, 1.28g potassium persulfate and 0.02g methylene bisacrylamide were added to the three-necked flask. After the addition, the system temperature was raised to 65°C, and the reaction was carried out at a temperature of 65°C for 1.5h. After the reaction was completed, the coconut fiber was filtered out, washed with deionized water, and then dried to obtain water-absorbent modified coconut fiber; Step 5, the water-absorbing modified coconut fiber is modified by low-temperature oxygen plasma and then added to a beaker containing an ethanol solution of a silane coupling agent, and the pH is adjusted to 4.5 with glacial acetic acid. After soaking for 1.5 hours at room temperature, the coconut fiber is filtered out, washed with deionized water, and then dried to obtain a silane coupling agent-modified coconut fiber. In this step, the mass fraction of the solute silane coupling agent in the ethanol solution of the silane coupling agent is 1%, and the solvent is an ethanol aqueous solution with a volume fraction of 95%. The silane coupling agent used is obtained by mixing KH-550 and a titanate coupling agent NDZ-201 in a mass fraction ratio of 1:1, and the mass fraction ratio of the water-absorbing modified coconut fiber and the silane coupling agent used is 1:6; Step 6, soaking the coconut fiber modified by the silane coupling agent in a beaker containing a nano-silicon dioxide dispersion for 2 hours, filtering out the coconut fiber after ultrasonic treatment for 0.5 hours and drying to obtain modified coconut fiber, wherein the dispersant used for the nano-silicon dioxide dispersion is polyvinyl pyrrolidone, and the solvent is deionized water, wherein the mass fraction of nano-silicon dioxide is 0.5%, the mass fraction of the dispersant is 1-5%, and the mass ratio of the used silane coupling agent modified coconut fiber to the nano material is 1:4.5.

[0031] Example 3 A modified coconut fiber is prepared by the following steps: Step 1, 0.1 mol 2-chloromethylbenzoic acid and 0.01 mol phosphorous acid are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, the system temperature is raised to 90°C, 13 g concentrated sulfuric acid is added dropwise to the three-necked flask, and after the addition is completed, the reaction is continued at a temperature of 90°C for 30 minutes. After the reaction is completed, the reaction solution is poured into deionized water for cooling and precipitation, and then vacuum filtered, and the obtained solid is recrystallized and dried to obtain a modifier; Step 2, the cut coconut fiber and the mass fraction of 5% sodium hydroxide solution are mixed in a three-necked flask at a mass ratio of 1:15, magnetic stirring is turned on, and the reaction is carried out at room temperature for 1h for alkalization treatment, and then the coconut fiber is filtered out, washed with deionized water and dried to obtain alkalized coconut fiber, and then the alkalized coconut fiber and the mass fraction of 3% hydrogen peroxide solution are mixed in a three-necked flask at a mass ratio of 1:20, magnetic stirring is turned on, and the reaction is carried out under outdoor conditions for 2h for oxidation treatment, and then the coconut fiber is filtered out, washed with deionized water and dried to obtain oxidatively modified coconut fiber; Step 3, the oxidatively modified coconut fiber and the isopropanol solution of the modifier with a mass fraction of 20% are mixed in a three-necked flask in a mass ratio of 7:15, magnetic stirring is turned on, and the reaction is carried out at a temperature of 60° C. for 1.5 hours. After the reaction is completed, the coconut fiber is filtered out, washed with deionized water, then washed with anhydrous ethanol, and dried to obtain etherified coconut fiber; Step 4, 20g etherified coconut fiber, 52g acrylic acid, 9.6g acrylamide, and 120mL deionized water were mixed in a three-necked flask, a condenser and a thermometer were installed, and magnetic stirring was turned on. Then, 1.28g potassium persulfate and 0.02g methylene bisacrylamide were added to the three-necked flask. After the addition, the system temperature was raised to 70°C, and the reaction was carried out at a temperature of 70°C for 2h. After the reaction was completed, the coconut fiber was filtered out, washed with deionized water, and then dried to obtain water-absorbent modified coconut fiber; Step 5, modifying the water-absorbent modified coconut fiber with low-temperature oxygen plasma, adding it to a beaker containing an ethanol solution of a silane coupling agent, and adjusting the pH to 5 with glacial acetic acid. After soaking for 2 hours at room temperature, filtering out the coconut fiber, washing it with deionized water, and drying it to obtain a silane coupling agent-modified coconut fiber. In this step, the mass fraction of the solute silane coupling agent in the ethanol solution of the silane coupling agent is 1%, and the solvent is an ethanol aqueous solution with a volume fraction of 95%. The silane coupling agent used is obtained by mixing KH-550 and a titanate coupling agent NDZ-201 in a mass fraction ratio of 1:1, and the mass fraction ratio of the water-absorbent modified coconut fiber and the silane coupling agent used is 1:6; Step 6, soaking the coconut fiber modified by the silane coupling agent in a beaker containing a nano-alumina dispersion for 2 hours, filtering out the coconut fiber after ultrasonic treatment for 0.5 hours and drying to obtain modified coconut fiber, wherein the dispersant used for the nano-alumina dispersion is polyvinyl pyrrolidone, and the solvent is deionized water, wherein the mass fraction of nano-alumina is 0.5%, the mass fraction of the dispersant is 1-5%, and the mass ratio of the silane coupling agent modified coconut fiber to the nanomaterial is 1:5.

[0032] Example 4 A crack-resistant plant fiber concrete comprises the following raw materials in parts by weight: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 23.2 parts of modified coconut fiber obtained in Example 1, 72 parts of S95 grade slag powder, 55 parts of Class F Class I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high-performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; A method for preparing crack-resistant plant fiber concrete comprises the following steps: The first step is to weigh the raw materials by mass: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 23.2 parts of modified coconut fiber obtained in Example 1, 72 parts of S95 grade slag powder, 55 parts of Class F Class I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; Step 2: Add PO 42.5 grade ordinary Portland cement, S95 grade slag powder, F class I fly ash, natural sand and 5mm-31.5mm continuously graded crushed stone into a forced mixer, dry mix for 30 seconds, add the modified coconut fiber obtained in Example 1 after mixing evenly, and continue dry mixing for 1 minute to obtain a mixture; Step 3: Dissolve RAWY101 polycarboxylic acid high-performance water reducing agent, FX-9 air entraining agent and UEA expansion agent with deionized water, stir them evenly and add them into a forced mixer filled with the mixture, wet mix for 1 minute to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers. The height of each layer of concrete after pouring is half of the test mold height. Vibrate and compact each layer of concrete mixture after pouring. Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

[0033] Example 5 A crack-resistant plant fiber concrete comprises the following raw materials in parts by weight: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 23.2 parts of modified coconut fiber obtained in Example 2, 72 parts of S95 grade slag powder, 55 parts of Class F Class I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high-performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; A method for preparing crack-resistant plant fiber concrete comprises the following steps: The first step is to weigh the raw materials by mass: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 23.2 parts of modified coconut fiber obtained in Example 2, 72 parts of S95 grade slag powder, 55 parts of Class F Class I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; Step 2: Add PO 42.5 grade ordinary Portland cement, S95 grade slag powder, F class I fly ash, natural sand and 5mm-31.5mm continuously graded crushed stone into a forced mixer, dry mix for 30 seconds, add the modified coconut fiber obtained in Example 2 after mixing evenly, and continue dry mixing for 1.5 minutes to obtain a mixture; Step 3: Dissolve RAWY101 polycarboxylic acid high-performance water reducing agent, FX-9 air entraining agent and UEA expansion agent with deionized water, stir them evenly and add them into a forced mixer filled with the mixture, wet mix for 1.5 minutes to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers. The height of each layer of concrete after pouring is half of the test mold height. Vibrate and compact each layer of concrete mixture after pouring. Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

[0034] Example 6 A crack-resistant plant fiber concrete comprises the following raw materials in parts by weight: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 23.2 parts of modified coconut fiber obtained in Example 3, 72 parts of S95 grade slag powder, 55 parts of Class F Grade I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high-performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; A method for preparing crack-resistant plant fiber concrete comprises the following steps: The first step is to weigh the raw materials by mass: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 23.2 parts of modified coconut fiber obtained in Example 3, 72 parts of S95 grade slag powder, 55 parts of Class F Class I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; Step 2: Add PO 42.5 grade ordinary Portland cement, S95 grade slag powder, F class I fly ash, natural sand and 5mm-31.5mm continuously graded crushed stone into a forced mixer, dry mix for 30 seconds, add the modified coconut fiber obtained in Example 3 after mixing evenly, and continue dry mixing for 2 minutes to obtain a mixture; Step 3: Dissolve RAWY101 polycarboxylic acid high-performance water reducing agent, FX-9 air entraining agent and UEA expansion agent with deionized water, stir them evenly and add them into a forced mixer filled with the mixture, wet mix for 2 minutes to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers. The height of each layer of concrete after pouring is half of the test mold height. Vibrate and compact each layer of concrete mixture after pouring. Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

[0035] Comparative Example 1 A crack-resistant plant fiber concrete comprises the following raw materials in parts by weight: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 72 parts of S95 grade slag powder, 55 parts of Class F Grade I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high-performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; A method for preparing crack-resistant plant fiber concrete comprises the following steps: The first step is to weigh the raw materials by mass: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 72 parts of S95 grade slag powder, 55 parts of Class F Class I fly ash, 7.5 parts of RAWY101 type polycarboxylic acid high performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; Step 2: Add PO 42.5 grade ordinary Portland cement, S95 grade slag powder, F class I fly ash, natural sand and 5mm-31.5mm continuously graded crushed stone into a forced mixer, and dry mix for 2.5 minutes to obtain a mixture; Step 3: Dissolve RAWY101 polycarboxylic acid high-performance water reducing agent, FX-9 air entraining agent and UEA expansion agent with deionized water, stir them evenly and add them into a forced mixer filled with the mixture, wet mix for 2 minutes to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers. The height of each layer of concrete after pouring is half of the test mold height. Vibrate and compact each layer of concrete mixture after pouring. Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

[0036] Comparative Example 2 A crack-resistant plant fiber concrete comprises the following raw materials in parts by weight: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 72 parts of S95 grade slag powder, 7.5 parts of RAWY101 type polycarboxylic acid series high-performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; A method for preparing crack-resistant plant fiber concrete comprises the following steps: The first step is to weigh the raw materials by mass: 230 parts of PO 42.5 grade ordinary Portland cement, 826 parts of natural sand, 985 parts of 5mm-31.5mm continuously graded crushed stone, 72 parts of S95 grade slag powder, 7.5 parts of RAWY101 type polycarboxylic acid high performance water reducer, 0.9 parts of FX-9 type air entraining agent, 23 parts of UEA expansion agent, and 121 parts of water; Step 2: Add PO 42.5 grade ordinary Portland cement, S95 grade slag powder, natural sand and 5mm-31.5mm continuously graded crushed stone into a forced mixer, and dry mix for 2.5 minutes to obtain a mixture; Step 3: Dissolve RAWY101 polycarboxylic acid high-performance water reducing agent, FX-9 air entraining agent and UEA expansion agent with deionized water, stir them evenly and add them into a forced mixer filled with the mixture, wet mix for 2 minutes to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers. The height of each layer of concrete after pouring is half of the test mold height. Vibrate and compact each layer of concrete mixture after pouring. Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

[0037] Experimental Example 1 The compressive strength and flexural strength of the anti-cracking plant fiber concrete in Examples 4-6 and Comparative Examples 1-2 were tested according to the national standard GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the concrete crack resistance was tested using the concrete shrinkage crack test method. The crack width gauge was used to regularly observe and record the crack development of the specimens during the curing period. The test results are shown in Table 1: Table 1 It can be seen from Table 1 that the crack-resistant plant fiber concrete of the present invention in Examples 4-6 has good compressive strength, flexural strength and crack resistance. Comparative Examples 1-2 respectively carried out control experiments on the modified coconut fiber and fly ash used in the preparation method of the present invention. It can be seen that the addition of fly ash can slightly improve the compressive strength and flexural strength of the concrete material, but has no effect on the width of shrinkage cracks. The addition of modified coconut fiber can effectively improve the compressive strength, flexural strength and crack resistance of the concrete material. In summary, the crack-resistant plant fiber concrete prepared by the preparation method of the present invention has good mechanical properties and crack resistance, and can be widely used in the field of building materials.

[0038] The above is a detailed introduction to a crack-resistant plant fiber concrete and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combination method. It should be pointed out that for ordinary technicians in this technical field, the present invention can also be improved and modified in a number of ways without departing from the principles of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be used in combination with each other in any way. The reason why these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A crack-resistant plant fiber concrete, characterized in that: The raw materials include the following parts by weight: 230 parts of cement, 826 parts of fine aggregate, 985 parts of coarse aggregate, 23.2 parts of modified coconut fiber, 72 parts of mineral powder, 55 parts of fly ash, 7.5 parts of water reducer, 0.9 parts of air entraining agent, 23 parts of expansion agent, and 121 parts of water; Wherein, the modified coconut fiber is prepared by the following steps: Step 1, 2-chloromethylbenzoic acid and phosphorous acid are mixed in a container, stirred evenly, the system temperature is raised to 80-90°C, concentrated sulfuric acid is then added dropwise to the container, and after the addition is complete, the reaction is continued at a temperature of 80-90°C for 30 minutes to obtain a modifier; Step 2, the cut coconut fiber and the sodium hydroxide solution are mixed in a container, stirred evenly, and reacted at room temperature for 1 hour to obtain alkalized coconut fiber, then the alkalized coconut fiber is added to a container filled with hydrogen peroxide solution, stirred evenly, and reacted under outdoor conditions for 2 hours to obtain oxidatively modified coconut fiber; Step 3, mixing the oxidatively modified coconut fiber and the isopropanol solution of the modifier in a container, stirring evenly, and reacting at a temperature of 50-60° C. for 1.5 hours to obtain the etherified coconut fiber; Step 4, etherified coconut fiber, acrylic acid, acrylamide, and deionized water are mixed in a container, and after stirring evenly, potassium persulfate and methylene bisacrylamide are added to a three-necked flask, and after the addition, the system temperature is raised to 60-70° C., and the reaction is carried out at a temperature of 60-70° C. for 1-2 hours to obtain water-absorbent modified coconut fiber; Step 5, adding the water-absorbent modified coconut fiber modified by low-temperature oxygen plasma into a container containing an ethanol solution of a silane coupling agent, adjusting the pH to 4-5 with glacial acetic acid, and soaking the solution at room temperature for 1-2 hours to obtain silane coupling agent modified coconut fiber; Step 6: Soak the coconut fiber modified by the silane coupling agent in a container containing a nanomaterial dispersion, and obtain the modified coconut fiber after ultrasonic treatment.

2. The anti-cracking plant fiber concrete according to claim 1, characterized in that: The concentrated sulfuric acid used in step 1 is concentrated sulfuric acid with a mass fraction of 98%, and the amount ratio of 2-chloromethylbenzoic acid, phosphorous acid and concentrated sulfuric acid used is 0.1 mol: 0.01 mol: 11-13 g.

3. The anti-cracking plant fiber concrete according to claim 1, characterized in that: In step 2, the specification of the coconut fiber after cutting is 20-30mm, the sodium hydroxide solution used is a sodium hydroxide aqueous solution with a mass fraction of 5%, and the mass ratio of the cut coconut fiber and the sodium hydroxide solution is 1:15; the hydrogen peroxide solution used is a hydrogen peroxide aqueous solution with a mass fraction of 3%, and the mass ratio of the alkalized coconut fiber and the hydrogen peroxide solution is 1:

20.

4. The anti-cracking plant fiber concrete according to claim 1, characterized in that: The mass fraction of the isopropanol solution of the modifier used in step 3 is 20%, and the mass ratio of the oxidatively modified coconut fiber and the isopropanol solution of the modifier used is 7:

15.

5. The anti-cracking plant fiber concrete according to claim 1, characterized in that: The amount ratio of the etherified coconut fiber, acrylic acid, acrylamide, deionized water, potassium persulfate and methylene bisacrylamide used in step 4 is 20g:48-52g:6-9.6g:100-120mL:1.28g:0.02g.

6. The anti-cracking plant fiber concrete according to claim 1, characterized in that: The conditions for oxygen plasma modification in step 5 are a power of 100 W and a modification time of 5-15 min; the mass fraction of the solute silane coupling agent in the ethanol solution of the silane coupling agent is 1%, the solvent is an ethanol aqueous solution with a volume fraction of 95%, the silane coupling agent used is obtained by mixing KH-550 and a titanate coupling agent NDZ-201 in a mass ratio of 1:1, and the mass ratio of the water-absorbent modified coconut fiber and the silane coupling agent used is 1:

6.

7. The anti-cracking plant fiber concrete according to claim 1, characterized in that: The nano material described in step 6 is one of nano silicon dioxide and nano aluminum oxide, the dispersant used for the nano material dispersion is polyvinyl pyrrolidone, the solvent is deionized water, the mass fraction of the nano material is 0.5%, the mass fraction of the dispersant is 1-5%, the mass ratio of the silane coupling agent modified coconut fiber to the nano material is 1:4-5, the immersion time is 2h, and the ultrasonic dispersion time is 0.5h.

8. A method for preparing a crack-resistant plant fiber concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: The first step is to weigh the raw materials according to the mass proportions: 230 parts of cement, 826 parts of fine aggregate, 985 parts of coarse aggregate, 23.2 parts of modified coconut fiber, 72 parts of mineral powder, 55 parts of fly ash, 7.5 parts of water reducer, 0.9 parts of air entraining agent, 23 parts of expansion agent, and 121 parts of water; Step 2: Add cement, mineral powder, fly ash, fine aggregate and coarse aggregate into a forced mixer, dry mix for 30 seconds, add modified coconut fiber after mixing evenly, and continue dry mixing for 1-2 minutes to obtain a mixture; Step 3: Dissolve the water reducing agent, air entraining agent and expansion agent with deionized water, stir them evenly, then add them into the forced mixer filled with the mixture, and wet mix for 1-2 minutes to obtain a concrete mixture; Step 4: Pour the concrete mixture into the mold in two layers, and vibrate and compact each layer of concrete mixture after pouring; Step 5. After pouring, cover the concrete surface with plastic film and let it stand for 24 hours before demoulding. After demoulding, cure the concrete specimen in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days to obtain a crack-resistant plant fiber concrete.

9. The method for preparing crack-resistant plant fiber concrete according to claim 8, characterized in that: The cement is PO 42.5 grade ordinary Portland cement, the fine aggregate is natural sand, the coarse aggregate is 5mm-31.5mm continuously graded crushed stone, the mineral powder is S95 grade slag powder, the fly ash is Class F Grade I fly ash, the water reducer is RAWY101 type polycarboxylic acid high performance water reducer, the air entraining agent is FX-9 type air entraining agent, and the expansion agent is UEA expansion agent.

10. The method for preparing crack-resistant plant fiber concrete according to claim 8, characterized in that: In the fourth step, the height of each layer of concrete after pouring is half of the test mold height.

Citation Information

Cited By

  • Synergistic modified bamboo fiber concrete and preparation method thereof

    CN122079562A